V. SOBOLEV KIMBERLITE PIPE (YAKUTIA): STRUCTURE AND COMPOSITION - Serov V.P.; Khar'kiv A.D.; Ustinov V.I.; Ukhanov A.V. (My University, 2005)
The geologic structure and lithology of the Sobolev kimberlite pipe and some other nearby pipes are considered. These pipes are buried beneath Upper Paleozoic terrigenous-sedimentary rocks intruded by trap sills. The total thickness of the overlying rocks reaches 80 m. The pipe kimberlites belong to a magnesian group. They are composed of autolith breccias typical of kimberlites of the Alakit-Markha field and have a low diamond potential. In addition to indicator minerals, the heavy fraction of kimberlites has elevated contents of almandine and ferriferous ilmenite, which were transported from schists of the platform basement. Despite the low diamond potential, the kimberlites often bear not only magnesian garnets and chromites but also subcalcic knorringite-bearing pyropes and chromites of diamond association. This is a typomorphic feature of garnets and chromites of kimberlites of the Daldyn-Alakite region.
Keywords: Кимберлитовые трубки; Алакит-Мархинское поле; индикаторные минералы кимберлитов; KIMBERLITE PIPES; ALAKIT-MARKHA FIELD; INDICATOR MINERALS OF KIMBERLITES; 549:552.323.6(571.56); Палеозой; Paleozoic